ANALISIS UNDANG-UNDANG NOMOR 6 TAHUN 2020 TENTANG PEMILIHAN GUBERNUR, BUPATI, DAN WALIKOTA TERKAIT AMBANG BATAS PENCALONAN KEPALA DAERAH UNTUK MEWUJUDKAN DEMOKRASI LOKAL YANG BERKUALITAS - Rizqika, Firda; Firdaus, Sunny Ummul (Res Publica: Jurnal Hukum Kebijakan Publik, 2023)
This study aims to analyze the threshold setting for Regional Head candidates in Law Number 6 of 2020, know the implications and analyze the threshold for realizing quality local democracy in order to obtain ideal threshold constructions in order to achieve quality local democracy. The type of research used is normative and applied prescriptive in nature. The results of this study indicate that the threshold for candidates for Regional Head in Law Number 6 of 2020 from the path of political parties or coalition of political parties has increased quite high, which implies weak guarantees of constitutional rights for citizens, limited alternative candidates, fragile coalitions, and governments that do not check and balance. Based on the value of democracy according to A.Dahl, the threshold has actually reduced the quality of democracy in terms of competition, participation and the fulfillment of political rights so it is important to remove the threshold for political parties.